2000
DOI: 10.1053/jvet.2000.4389
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antibiotic Elution from Polymethylmethacrylate (PMMA) and Mechanical Assessment of Antibiotic‐PMMA Composites

Abstract: Bacteria introduced during a surgical procedure may be inhibited by elution of antibiotic from PMMA at the time of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
4
41
0
1
Order By: Relevance
“…Agar diffusion is the most common in vitro testing method for studying the antimicrobial activities of loaded bone cement samples (23,27). The correlation of the MICs of gentamicin determined by agar gel tests and the proliferation behavior of bacteria in the proliferation assay of the present study showed the accuracy of this new testing method.…”
Section: Figsupporting
confidence: 61%
See 1 more Smart Citation
“…Agar diffusion is the most common in vitro testing method for studying the antimicrobial activities of loaded bone cement samples (23,27). The correlation of the MICs of gentamicin determined by agar gel tests and the proliferation behavior of bacteria in the proliferation assay of the present study showed the accuracy of this new testing method.…”
Section: Figsupporting
confidence: 61%
“…Therefore, testing the antimicrobial activity of bone cement with new antibiotics or other antimicrobial agents should begin with in vitro studies. Agar diffusion testing has been the standard method for many years for in vitro assessment of antibiotic-loaded bone cements (17,23,27,28). However, the assessment by agar diffusion testing of the anti-infective activities of some antimicrobial agents requires accurately defined standard conditions (20).…”
mentioning
confidence: 99%
“…The greater the antibiotic concentration the bigger the antibiotic domains from which rupture initiates. [32][33][34][35] In general, the compression strength is not affected by small additions of antibiotics. 31,32,35,36 However, at higher percentages, this parameter can decrease below the minimum required by the ISO standard (70 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The effect is more noticeable in flexural tests 34,36 and, above all, in fatigue tests, since in these assays there is a significant decrease of the fatigue life with the addition of small quantities of antibiotics to the cement formulation. 32,33,37 With the aim of minimizing the detrimental effects of the addition of antibiotics, some authors recommend the use of commercial formulations with antibiotics included. These formulations are more consistent and homogeneous than hand-mixed ones, which can show lower strengths.…”
Section: Discussionmentioning
confidence: 99%
“…8 A study by Weisman et al evaluating the mechanical strength of antibiotic free cement and antibiotic impregnated cement using compression and elongation revealed a 32% decrease in compressive and tensile strength when the antibiotic powder was added to the liquid monomer compared to a 7% decrease in both when the antibiotic powder was added to the powdered polymer. 13 The mechanical strength of the PMMA is of outmost importance when used for arthroplasties, but not for AIPMMA bead production.…”
mentioning
confidence: 99%